2010
DOI: 10.3748/wjg.v16.i41.5225
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography: A non-invasive tool for assessing liver fibrosis in HIV/HCV patients

Abstract: ALF was more frequent in co-infected than mono-infected patients. This result correlated with lower CD4 levels. Protective immunological effects of HAART on LF progression outweigh its hepatotoxic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Liver fibrosis was assessed by a single certified operator (trained by the manufacturer) using transient elastography (FibroScan 1 ; EchoSens, Paris, France), as previously described. 27 Transient elastography provides an assessment of liver stiffness (LS) expressed in units of kPa.…”
Section: Liver Fibrosis Assessmentmentioning
confidence: 99%
“…Liver fibrosis was assessed by a single certified operator (trained by the manufacturer) using transient elastography (FibroScan 1 ; EchoSens, Paris, France), as previously described. 27 Transient elastography provides an assessment of liver stiffness (LS) expressed in units of kPa.…”
Section: Liver Fibrosis Assessmentmentioning
confidence: 99%
“…Details of the technical background and examination procedure have previously been described [21]. Liver cirrhosis was defined as liver stiffness ≥ 12.5 kPa [22].…”
Section: Liver Fibrosis Assessmentmentioning
confidence: 99%
“…However, liver biopsy is impractical for serial evaluations and not applicable in longitudinal cohort studies that require multiple evaluations of LF. Transient elastography could have been an alternative tool, [32] but this technique has become available only in recent years, thus limiting the length of follow-up; moreover, this tool could not have been applied to such a large population for practical reasons, and furthermore, elastography may be affected by operator-based biases. Despite a recent study found that noninvasive markers are not optimal, [20] these markers were already validated for estimating LF [13] and predicted hepatic decompensation and death in cohorts of patients.…”
Section: Discussionmentioning
confidence: 99%